Natural Disturbance-Based Forest Management: Moving Beyond Retention and Continuous-Cover Forestry - Kuuluvainen, Timo; Angelstam, Per; Frelich, Lee; Jõgiste, Kalev; Koivula, Matti; Kubota, Yasuhiro; Lafleur, Benoit; Macdonald, Ellen (Frontiers in Forests and Global Change, 2021)
Global forest area is declining rapidly, along with degradation of the ecological condition of remaining forests. Hence it is necessary to adopt forest management approaches that can achieve a balance between (1) human management designs based on homogenization of forest structure to efficiently deliver economic values and (2) naturally emerging self-organized ecosystem dynamics that foster heterogeneity, biodiversity, resilience and adaptive capacity. Natural disturbance-based management is suggested to provide such an approach. It is grounded on the premise that disturbance is a key process maintaining diversity of ecosystem structures, species and functions, and adaptive and evolutionary potential, which functionally link to sustainability of ecosystem services supporting human well-being. We review the development, ecological and evolutionary foundations and applications of natural disturbance-based forest management. We compare this approach with two main practices employed for sustainable forest management, retention and continuous-cover forestry. We conclude that these approaches potentially fail to achieve broad sustainability because they are not compatible with current understanding of multiple-scale ecological processes and structures, which underlie biodiversity, resilience and adaptive potential of forest ecosystems. Compared with retention and continuous-cover forestry, natural disturbance-based management provides a more comprehensive framework for reconciling human needs of commodity production and immaterial values with nature’s self-organized properties promoting healthy, diverse, and resilient forest ecosystems in the rapidly changing global environment.